Assessment Practices in the Kindergarten Stage in Light of Professional Standards from the Perspective of Kindergarten Teachers (Journal of the College of Education for Women, 2025)
The study aimed to identify the assessment practices required for kindergarten teachers in light of professional standards. It also sought to determine the extent to which these standards are met in the assessment practices of kindergarten teachers. To achieve the research objectives, the descriptive-analytical approach was used, and a questionnaire was applied to a sample of 80 kindergarten teachers in the cities of Khamis Mushait and Abha. The study found that teachers demonstrated a beginner level in managing learning situations that encourage activities for expressing opinions, providing opportunities, and utilizing them for creative activities that develop critical and creative thinking in preschool children. However, the first indicator—expressing opinions in storytelling activities—showed a very high level. The study also highlighted the importance of kindergarten teachers presenting activities in an engaging and enjoyable manner with children's participation, as well as training them to listen attentively to others, which achieved an ideal level. Additionally, indicators related to teachers' ability to attract attention, encourage participation and experimentation, engage in recreational activities and competitions, and treat children without discrimination achieved a very high level.The study recommended focusing on the practical and field aspects in early childhood education curricula in a way that ensures the desired outcomes of adopting professional standards. It also emphasized the importance of preparing for field training using various methods, such as micro-teaching, observation lessons, and meetings with experienced teachers.